2023
DOI: 10.18502/ijps.v18i2.12371
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among Military Personnel: A systematic Review

Abstract: Objective: Burnout is a psychological symptom characterized by emotional exhaustion, depersonalization, and lack of personal accomplishment. Several systematic reviews have examined the prevalence of burnout in some communities, including the communities of physicians, nurses, students, and teachers. Risk factors, consequences of burnout, and related interventions have also been evaluated in several systematic review studies. The purpose of this systematic review was to investigate the prevalence, risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Although critical stress responses can offer short-term benefits by providing the essential physiological and cognitive boosts required in combat situations, the transition to chronic stress poses significant risks. The repetition of acute stressors in a military context may propel soldiers into a state of chronic stress, where they persist in a heightened state of alertness and stress response, even in the absence of immediate threats [ 59 ]. This prolonged state has the potential to severely impair cognitive functions over time, diminishing operational effectiveness and escalating the risk of long-term health problems.…”
Section: Enduring the Unseen Battle: Acute And Chronic Stress And Fat...mentioning
confidence: 99%
“…Although critical stress responses can offer short-term benefits by providing the essential physiological and cognitive boosts required in combat situations, the transition to chronic stress poses significant risks. The repetition of acute stressors in a military context may propel soldiers into a state of chronic stress, where they persist in a heightened state of alertness and stress response, even in the absence of immediate threats [ 59 ]. This prolonged state has the potential to severely impair cognitive functions over time, diminishing operational effectiveness and escalating the risk of long-term health problems.…”
Section: Enduring the Unseen Battle: Acute And Chronic Stress And Fat...mentioning
confidence: 99%
“…Military operations are characterized by long working hours, heavy workloads, and a high level of responsibility, all of which may contribute to burnout [ 16 ]. A systematic review has revealed that the prevalence of high burnout among soldiers ranges from 0.9% to 40% [ 17 ]. A survey conducted by the Brazilian Air Force found that 86.7% of military professionals serving as Air Traffic Controllers experienced burnout [ 18 ].…”
Section: Introductionmentioning
confidence: 99%